Do They Adapt or Collapse?Digital Immigrants to Digital Communication Technology during the Pandemic of Covid-19 - Mohd Yusof Zulkefli; Ahmad Farid Abdul Fuad; Mohd Nor Azren Kamarudin; Nathasha Diyana Zulkifly; Abdul Hamid Saifuddin (USIM Press, 2024)
Vol. 2 No. 2 (2022) Page(75-85)